Stent thrombosis and adverse cardiovascular outcomes observed between six months and five years with sirolimus-eluting stents and other drug-eluting stents in patients with Type 2 diabetes mellitus complicated by coronary artery disease: A systematic review and meta-analysis. Issue 27 (July 2016) - Bundhun, Pravesh Kumar; Soogund, M. Zafooruddin Sani; Pursun, Manish; Chen, Meng-Hua
Abstract : Abstract: This study aimed to compare 6 months to 5 years stent thrombosis (ST) and adverse cardiovascular outcomes associated with sirolimus-eluting stents (SES) and other drug-eluting stents (DES) in patients with type 2 diabetes mellitus (T2DM). Electronic databases were searched for studies comparing SES with other DES in patients with T2DM. Total ST, definite ST, probable ST, and other adverse cardiovascular outcomes reported between 6 months and 5 years were considered as the clinical end points in this study. Odds ratios (ORs) with 95% confidence intervals (CIs) were calculated for categorical variables and the pooled analyses were performed with RevMan 5.3 software. Twenty-nine studies involving a total number of 25, 729 patients with diabetes were included in this meta-analysis. SES were not associated with significantly higher total, definite, and probable STs with OR: 0.95, 95% CI: 0.77–1.17, P = 0.62; OR: 0.94, 95% CI: 0.65–1.37, P = 0.76; and OR: 1.05, 95% CI: 0.77–1.45, P = 0.74, respectively. SES were also noninferior to the other non-sirolimus eluting drug eluting stents (non-SE DES) in terms of all-cause mortality, cardiac death, myocardial infarction, and stroke with OR: 0.92, 95% CI: 0.82–1.03, P = 0.16; OR: 1.09, 95% CI: 0.88–1.35, P = 0.44; OR: 0.92, 95% CI: 0.80–1.06, P = 0.26; and OR: 0.79, 95% CI: 0.49–1.28, P = 0.43, respectively. Target vessel revascularization, target lesion revascularization, and major adverse cardiac events were also similarly reported between SES and non-SE DES with OR: 1.04, 95% CI: 0.83–1.31, P = 0.72; OR: 1.25, 95% CI: 0.95–1.64, P = 0.11; and OR: 1.06, 95% CI: 0.90–1.25, P = 0.49, respectively. During this particular follow-up period, SES were not associated with any increase in ST among these patients with T2DM. Mortality and other adverse cardiovascular outcomes were also not significantly different between these 2 groups. Hence, SES should be considered neither superior nor inferior to other DES. They are expected to be equally effective and safe to use in patients with T2DM.